Pathologic and immunohistochemical prognostic markers in residual triple-negative breast cancer after neoadjuvant chemotherapy - Ilie, Silvia Mihaela; Briot, Nathalie; Constatin, Guillaume; Ilie, Alis; Beltjens, Francoise; Ladoire, Sylvain; Desmoulins, Isabelle; Hennequin, Audrey; Bertaut, Aurelie; Coutant, Charles; Causeret, Sylvain; Ghozali, Niama; et al. (Frontiers in Oncology, 2024)
The persistence of residual tumour after neoadjuvant chemotherapy (NAC) in localized triple negative breast cancer (TNBC) is known to have negative prognostic value.However, different degrees of expression of some immunohistochemical markers may correlate with different prognoses.The expression of biomarkers with known prognostic value, i.e. cytokeratin 5/6 (CK5/6), androgen receptor (AR), epidermal growth factor receptor (EGFR) proliferationrelated nuclear antigen KI67, human epidermal growth factor receptor 2 (HER2), p53, forkhead box P3 (FOXP3) and cluster differentiation 8 (CD 8) were analysed by immunohistochemistry in 111 samples after NAC in non-metastatic TNBC patients addressed to Georges-François Leclerc Cancer Centre Dijon, France. Clinical and pathological variables were retrospectively collected. Cox regression was used to identify IHC and clinicopathological predictors of event-free survival (relapse or death) (EFS).Median age was 50.4 years (range 25.6-88.3), 55.9% (N=62) were non-menopausal, 70 (63.1%) had stage IIA-B disease. NAC was mostly sequential anthracycline-taxanes (72.1%), and surgical intervention was principally conservative (51.3%). We found 65.7% ypT1, 47.2% lymph node involvement (ypN+) and 29.4% lymphovascular invasion (LVI).Most residual tumours were EGFR >110 (H-score) (60.5%, n=66), AR ≥4% (53.2%, n=58), p53 positive mutated (52.7%, n=58), CD8≥26 (58.1%, n=61), FOXP3 ≥7(51.4%, n= 54), more than half in the stroma, and 52.3% (n=58) HER2 score 0. After a median follow-up of 80.8 months, 48.6% had relapsed. Median EFS was 62.3 months (95% CI, 37.2-NR). Factors independently associated with poor EFS were AR-low (p=0.002), ypN+ (p < 0.001) and LVI (p=0.001). Factors associated with lower overall survival (OS) were EGFR-low (p=0.041), Ki67 high (p=0.024) and ypN+ (p<0.001).Conclusions Post-NAC residual disease in TNBC showed biomarkers specific to a basal-like subtype and markers of lymphocyte infiltration mostly present in the stroma. Prognostic markers for EFS were AR, LVI and ypN, and warrant further validation in a prognostic model.